Perbandingan Strategi Tipe Listening Team dengan Tipe Practice Rehearsal Pairs - via, ilta (Kopertis Wilayah X (Sumbar, Riau, Jambi, dan Riau Kepulauan), 2018)
Mathematics is one of the lessons learned in school to develop the ability to count, measure, and solve problems in everyday life. Math grows due process of thinking, therefore, the logic is the basis for the formation of mathematics. Logic is the infancy of mathematics, mathematics is the opposite of logic adulthood. Given the importance of mathematics in life, we need a learning that is able to develop students' mathematical abilities. through the practice of acting on the premise logical, rational, critical, careful, honest, effective and efficient. And to prepare students to use mathematics and mindset of mathematics in everyday life, and in studying various sciences. Efforts should be made to overcome this problem is by applying active learning strategies that can help the learning process of students that is based on the creativity of the students active learning strategies Listening Team and the type of active learning strategies type Practice Rehearsal Pairs. This study aims to determine differences in learning outcomes of students who are taught using active learning strategies Listening Team and the type of active learning strategies type Practice Rehearsal Pairs